KINERJA KARYAWAN DAN IMPLIKASINYA TERHADAP LAYANAN KONSELING - Dewi, Rosdiana; Khairani, Khairani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractPerformance is a comparison of work results achieved by employees  with predetermined standards. This study aims to   (1) describeing the performance seen from the aspects of quality and quantity (2) describeing the performance seen from the aspects of discipline. (3) describeing the performance seen from the aspect of cooperation (4) describeing the performance seen from the aspect of  personality (5) desribeing the performance seen from the aspect of respontability. This type of research is quantitative descriptive. The research subjects were employees of PT. PLN (PERSERO) Rayon LubukBasug which numbered 54 people. The instrument used were questionnaires and analyzed by percentage techniques. Research findings show that employee performance results seen from (1) aspect of quality and quantity are in good category (2) discipline aspect are in good category (3) aspects of cooperation are in good category (4) aspects of personality are in good category (5) and aspects of respontability are in good category.  Keyword: Performance